U.S. pregnant women's knowledge and attitudes about behavioral strategies and vaccines to prevent Zika acquisition. Issue 1 (2nd January 2018) - Fraiz, Lauren Dapena; de Roche, Ariel; Mauro, Christine; Catallozzi, Marina; Zimet, Gregory D.; Shapiro, Gilla K.; Rosenthal, Susan L.
Highlights: Most (74%) pregnant women expressed concerns about the Zika virus. Low perceived knowledge of Zika corresponded to low factual knowledge. Developing a Zika vaccine was very important to the majority (72%) of respondents. Women (38%) supported a universal strategy that would vaccinate men and women. Abstract: Introduction: Zika virus infection during pregnancy can cause significant infant morbidity. Little is known about pregnant women's attitudes regarding behavioral strategies and hypothetical vaccination to prevent Zika infections and sequelae. Methods: Pregnant women across the United States (N = 362) completed an online questionnaire regarding attitudes about Zika, including six behavioral prevention strategies (i.e., abstaining from sex, using condoms, not traveling to an area with Zika, their partner not traveling into an area with Zika, using mosquito repellant, wearing long pants and sleeves) and vaccination. Results: Most women (91%) were married/living with the baby's father, 65% were non-Hispanic White, and 71% had been pregnant. Seventy-four percent were worried about Zika, while 30% thought they were knowledgeable about Zika. The mean knowledge score was 5.0 out of 8 (SD = 2.09), and the mean behavioral strategies score was 4.9 out of 12 (SD = 3.7) with a range of 0 (none would be hard to do) to 12 (all would be hard to do). In a multivariable model, having had a sexually transmitted infection, living/traveling in an area with Zika, and worrying about Zika were significantly related to reporting behavioral strategies as hard to do. Seventy-two percent would be willing to be vaccinated. In the multivariable model, living/traveling in an area with Zika, believing they knew a lot about Zika, worrying about Zika, and considering Zika vaccine development as important were significantly associated with willingness to get vaccinated. Conclusions: Pregnant women were worried about Zika, yet had gaps in their factual knowledge. Most women reported they would get vaccinated if a vaccine was available. Pregnant women who reported themselves as vulnerable (being worried, having lived in or traveled to a Zika area) were more likely to view behavioral strategies as hard to do and to accept vaccination.